Dental fluorosis among people and livestock living on Gihaya Island in Lake Kivu, Rwanda - Theodore Habiyakare; Janna M. Schurer; Barika Poole; Susan Murcott; Basile Migabo; Birori Mardochee; J. Hellen Amuguni; John P. Morgan (BMC, 2021)
Abstract Background Dental fluorosis is caused by prolonged exposure to excessive fluoride during the period of permanent tooth formation and is characterized by tooth discoloration, pitting, and loss of shape. Communities living near Lake Kivu in Western Rwanda exhibit a high prevalence of dental fluorosis; however, data on prevalence and risk factors are scarce. Methods This cross sectional, quantitative study used a One Health approach to investigate dental fluorosis prevalence among people and livestock and to measure fluoride content in the environment. In 2018, oral health examinations were conducted to assess the prevalence of fluorosis in children (aged 9 to 15 years), cattle and goats residing on Gihaya Island (Rwanda, East Africa). All children and cattle/goats meeting basic eligibility criteria (e.g., island residence) were invited to participate. Presence and severity of dental fluorosis was categorized according to the Dean's Fluorosis Index. Samples of local foods, water, soil and grass were collected from communal sources and individual households and analyzed for fluoride content using standard laboratory techniques. Descriptive and binomial analyses (Fisher Exact Test) were used to assess this dataset. Results Overall, 186 children and 85 livestock owners (providing data of 125 livestock -23 cattle and 102 goats) participated. Dental fluorosis was recorded in 90.7% of children and 76% of livestock. Moderate to severe fluorosis was observed in 77% children while goats and cattle most often exhibited mild or absent/questionable severity, respectively. Water from Lake Kivu (used primarily for human cooking water and livestock drinking water) contained fluoride levels that were consistently higher than the maximum threshold (1.5 mg/L) recommended by the World Health Organization. Other sources (borehole and rainwater) were within safe limits. All food, soil and grass samples contained fluoride. The highest levels were observed in porridge (0.5 mg/g) and small fishes (1.05 mg/g). Conclusions Altogether, dental fluorosis was highly prevalent among children and goats on Gihaya Island with various food and water sources contributing a cumulative exposure to fluoride. An immediate and coordinated response across human, animal and water professionals is needed to reduce fluoride exposure within safe limits for island residents.